2021
DOI: 10.1111/ctr.14509
|View full text |Cite
|
Sign up to set email alerts
|

Increase in nuclear cell‐free DNA is associated with major adverse events in adult and pediatric heart transplant recipients

Abstract: Background: Cell-free DNA is an emerging biomarker. While donor fraction may detect graft events in heart transplant recipients, the prognostic value of total nuclear cellfree DNA (ncfDNA) itself is largely unexplored.Objective: Explore the relationship between ncfDNA and clinical events in heart transplant recipients. Methods:We conducted a multi-center prospective study to investigate the value of cell-free DNA in non-invasive monitoring following heart transplantation. Over 4000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…As for dd-cfDNA, a preliminary study (Zangwill, 2020) [ 18 ] focused on the first 10 days after heart transplantation in a small pediatric population showed that a blunted decline of initially elevated dd-cfDNA may be associated with early death. Two other studies found that total cfDNA levels greater than 50 ng/mL were associated with increased risk of major events (composite outcome of cardiac arrest, mechanical circulatory support, death) (Zangwill 2022 [ 19 ]), death (Scott, Zangwill 2022 [ 19 , 20 ]) and treatment for infection [ 19 , 20 ].…”
Section: Pico Questions and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for dd-cfDNA, a preliminary study (Zangwill, 2020) [ 18 ] focused on the first 10 days after heart transplantation in a small pediatric population showed that a blunted decline of initially elevated dd-cfDNA may be associated with early death. Two other studies found that total cfDNA levels greater than 50 ng/mL were associated with increased risk of major events (composite outcome of cardiac arrest, mechanical circulatory support, death) (Zangwill 2022 [ 19 ]), death (Scott, Zangwill 2022 [ 19 , 20 ]) and treatment for infection [ 19 , 20 ].…”
Section: Pico Questions and Recommendationsmentioning
confidence: 99%
“…Of note, several groups have found clear relationships between “total or nuclear cfDNA” (derived both from recipient and donor tissues) and several near-term events, such as death, cardiac arrest, and need for mechanical circulatory support [ 19 ]. Total cfDNA seems to be a marker of more extensive tissue damage, and has demonstrated prognostic value in different ICU patient populations.…”
Section: Pico Questions and Recommendationsmentioning
confidence: 99%
“…Lastly, it has to be noted that the use of cell-free DNA in children poses additional problems, linked to the possibility of obtaining enough material from liquid biopsies and to optimizing cut-offs for this population. Recent data, however, have confirmed that in heart transplant recipients, children behave similarly to adults, with cfDNA being a very accurate predictor of rejection episodes [ 70 , 71 ]. The experience with kidney transplants is far more limited, and more studies with larger patient cohorts and longer follow-up are needed determine the impact of dd-cfDNA monitoring during routine follow-up of kidney-transplanted patients (Fig.…”
Section: Biomarkers Of the Future (Table 1 And Fig...mentioning
confidence: 99%